Improving the Quality of Learning Through Laboratory Infrastructure facilities at Sma Negeri 1 Polokarto - Utomo, David Hario; Azzahra, Afifah; Dewi, Mafida Kumala; Kusumawati, Ike; MS Khabiburrahman, MS Khabiburrahman MS Khabiburrahman (Journal of Geography Science and Education, 2021)
This research aims to improve the quality of learning through laboratory infrastructure facilities at Sma Negeri 1 Polokarto. This research uses a qualitative approach with a type of descriptive approach. The subjects in this study are the heads of biology laboratories, chemical laboratories, physics laboratories, and computer laboratories. Methods of collecting data by means of observation, interview, and documentation. Infrastructure facilities data obtained then compared to the standards that have been determined based on Permendiknas No. 24 of 2007. The results showed that 1.) The laboratory is an important part of the learning process. 2.) Overall the laboratory at Sma Negeri 1 Polokarto has met permendiknas standard No. 24 of 2007. 3.) Chemical and computer laboratory facilities are complete or adequate. 4.) Lack of complete equipment in biology and physics laboratories. 5.) There are several procurement of facilities and infrastructure that are not carried out from the school to the government.